(untitled) (Research, Society and Development, 2022)
This study deals with the legal characterization of the condition of “author” in innovation projects developed in the academic environment. Conducted through a bibliographic and legislative review, the research points to the importance of a clear understanding, by all those involved in R,D&I projects, regarding the legal criteria that determine the authorial recognition of aesthetic and technical creations, carried out at Universities. In this context, the importance of records at the beginning and during the execution of innovation projects is also highlighted, which identify the participants involved, as well as reveal the nature of the activities carried out, in order to provide conditions for effective and legitimate authorial characterization, considering the provisions of article 13 of Law No. 10,973/2004, as well as items I and II of Article 24 of Law No. 9,610/1998.